ATTITUDE TOWARDS WOMEN IN THE UZBEKISTAN SSR AND FIRST FEMALE HISTORIANS (World Bulletin of Social Sciences, 2024)
This article analyzes the attitude towards women in the Uzbekistan SSR, as well as the life and scientific activity of early female historians.